Escaping From Death Reflectd In David R. Ellis's Final Destination 4 (2009) Movie: A Psychoanalytic Approach - Daryani, Miftahul Izza, Dr. Phil. Dewi Candraningrum, S.Pd. M. Ed, Anam Sutopo,Spd, M.Hum (2013)
The major problem of this study is how anxiety is reflected in the major character‟s personality. The aim of this study is to analyze David Richard Ellis's Final Destination 4 based on the structural elements and the development of personality of the major character based on Psychoanalytic Approach. This study focuses on the major character, namely Nick Obanon. This research is qualitative research. The data of the study are text and image taken from two data sources: primary and secondary. The primary data source is the Final Destination movie directed by David Richard Ellis released in 2009. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en scene, cinematography, sound, and editing are related to each other and form a unity. Second, based on the psychoanalytic perspective that the problems of the major character cause the conflict of his mental condition. It happens when there is contradiction between Id, Ego, and Superego and it brings him into anxiety.